A new module in the drug development process: preclinical multi-center randomized controlled trial of R-ketamine on alcohol relapse - Meinhardt, Marcus W.; Skorodumov, Ivan; Jeanblanc, Jérôme; Benvenuti, Federica; Hilal, Fahd François; Domi, Esi; André, Camille; Bodeau, Sandra; Jeanblanc, Virginie; Domanegg, Kevin; Ciccocioppo, Roberto; Naassila, Mickael; et al. (Neuropsychopharmacology, 2025)
The drug development process in psychiatry faces significant challenges due to low reproducibility rates in animal testing, which often leads to translation failures. To address this issue, we introduce a new approach in psychiatric drug development: a preclinical randomized controlled trial (preRCT). To demonstrate its potential utility, we conducted a multi-center preRCT using the alcohol deprivation effect (ADE) model to assess the impact of ketamine and R-ketamine on alcohol relapse across three European research centers. Ketamine (20 mg/kg) significantly reduced relapse, while R-ketamine showed efficacy only in females. A higher dose of R-ketamine (40 mg/kg) was also effective in males. These sex-dependent effects were linked to plasma R-ketamine levels, which were two-fold higher in female compared to male rats. Notably, R-ketamine demonstrated a lasting reduction in alcohol consumption without adverse effects. In conclusion, our preRCT demonstrates R-ketamine’s effectiveness in reducing alcohol relapse and supports translation to a clinical RCT that accounts for sex-dependent effects.